Peningkatan Aktivitas Belajar Ekonomi Melalui Model Pembelajaran Problem Based Learning di Kelas X2 SMAN 17 Surabaya - Wahyuni, Yefi Indah; Dewi, Retno Mustika; Marsia, Yemi (Business and Accounting Education Journal, 2023)
The learning process in the classroom is not always successful, sometimes it experiences many obstacles or difficulties, influenced by various factors, ranging from interest in learning and models and methods in learning. In the initial observations that the researchers made, it was shown that X-2 students at SMAN 17 Surabaya had learning activities in economics lessons which were still relatively low, namely 61.9%. This class action research (CAR) aims to increase economic learning activities using the problem based learning model in class X-2 SMAN 17 Surabaya. This PTK research uses a collaborative model that is carried out for two cycles. As for the results, it can be concluded that the implementation of the problem-based learning model can increase economic learning activities in class X-2 students at SMAN 17 Surabaya. This is evidenced by an increase in the aspects of activity indicators in the learning process in the form of physical activity, mental activity and emotional activity where the average data on the results of each cycle there is an increase, namely in the activity of the first cycle the student's learning activity score was 70.0%. Then in cycle II activities experienced an increase with a learning activity score of 81.4%.